Small intestinal metastasis from primary breast cancer: a case report and review of literature - Shen, Fengqing; Wang, Songxiang; Yu, Shanlu; Jiang, Yuancong (Frontiers in Immunology, 2024)
Small intestinal metastasis from primary breast cancer remains a rare clinical occurrence. Despite extensive research into its clinicopathological features and treatment options, the specific pathogenesis and optimal management strategies remain incompletely understood. This case report presents a patient with breast cancer that metastasized to the small intestine. The primary breast tumor was diagnosed as classic invasive lobular carcinoma. Subsequent surgical intervention successfully addressed the intestinal obstruction and confirmed the metastatic origin of the small intestinal tumor. Interestingly, the metastatic lesions exhibited features suggestive of pleomorphic lobular carcinoma. A PET-CT scan was performed to evaluate the distant metastasis status of this patient. Notably, hormonal receptor status shifted from positive to negative, while HER2 expression changed from negative to low between the primary tumor and metastatic lesions. The presence of an undiagnosed pleomorphic component in the primary tumor might explain the disease’s progressive nature. In this case, systemic treatment with trastuzumab deruxtecan yielded favorable therapeutic outcomes. Overall, our findings suggest that re-evaluation of receptor status in breast cancer metastases is crucial for tailoring treatment strategies. Furthermore, a combination of palliative resection of small intestinal metastases and targeted therapy for HER2-low breast cancer may potentially improve survival.